The Impacts of the Global Financial Crisis on Stock Market Integration and Hedging Effectiveness : Evidence from Six Selected Asian Markets - Mponeja, Grace Faustine (2013)
The 2007-2009 Global Financial Crisis (GFC) is documented to have marked a tremendous decline in Asian stock market prices and, at the same time, increased the trading volume of the Asian stock index futures contracts. While this decline in stock markets has brought an eminent concern on the Asian stock market integration with developed markets like the US, the increase in trading volume of stock index futures has raised a special interest to know how effective these Asian futures markets were in minimizing the elevated price risk in their underlying stock indices during the GFC. Using daily closing stock and futures prices from 28th April, 2006 to 30th December, 2011, sub-divided into three periods, this paper first employs the Johansen’s (1991) Cointegration test and Generalized Impulse Response analysis in attempts to analyze how the crisis affected the stock market integration among the US and six Asian stock markets. Subsequently, it assesses the hedging effectiveness of these Asian futures markets during the GFC by employing both constant and time-varying hedge models to estimate the MVHR in each sub-period as well as the entire period. The study finds out that the GFC increased the level of financial integration between the US and the selected Asian markets. Moreover, unlike other markets, the Malaysian futures market was the least effective in mitigating the systematic risk in its underlying spot position during the crisis period while Singapore was the most effective in risk reduction during the crisis period. In addition, the study favors time varying hedge ratios estimated by DVEC M-GARCH model to yield better results, in terms of providing the highest return-to-variability ratio, in all futures markets except Singapore where the BVECM model is found superior. Overall, the study findings and analyses render important implications that there should be policies which monitor the extent of financial integration among the Asian stock markets and developed markets as to avoid severe costs associated with these markets being too vulnerable to external crises. Moreover, efficiency of developing stock index futures such as the Malaysia KLCI futures could possibly be enhanced by increasing liquidity of the markets through trading programs that readily provide trading information to potential investors and also reduction of transaction costs.